Improved measurement of time-dependent CP asymmetries and the CP-odd fraction in the decay B-0 -> D*D+*(-) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Garra Tico, J; Grauges, E; Lopez, L; et al. (2007)
We present an updated measurement of the CP-odd fraction and the time-dependent CP asymmetries in the decay B0→D*+D*- using (383±4)×106BB̄ pairs collected with the BABAR detector. We determine the CP-odd fraction to be 0.143±0.034(stat)±0.008(syst). The time-dependent CP asymmetry parameters are determined to be C+=-0.05±0.14(stat)±0.02(syst) and S+=-0.72±0.19(stat) ±0.05(syst). The nonzero value of the measured S+ indicates the evidence of CP violation at the 3.7σ confidence level. © 2007 The American Physical Society.